2018
DOI: 10.1128/jvi.01861-17
|View full text |Cite
|
Sign up to set email alerts
|

Digitoxin Suppresses Human Cytomegalovirus Replication via Na + , K + /ATPase α1 Subunit-Dependent AMP-Activated Protein Kinase and Autophagy Activation

Abstract: Host-directed therapeutics for human cytomegalovirus (HCMV) requires elucidation of cellular mechanisms that inhibit HCMV. We report a novel pathway used by cardiac glycosides to inhibit HCMV replication: induction of AMP-activated protein kinase (AMPK) activity and autophagy flux through the Na,K/ATPase α1 subunit. Our data illustrate an intricate balance between the autophagy regulators AMPK, mammalian target of rapamycin (mTOR), and ULK1 during infection and treatment with the cardiac glycoside digitoxin. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…These pathways include mitogen-activated kinase (MAPK) signalling both via extracellular signal-regulated kinase (ERK) 1 and 2 including RAF1 (MAPKKK upstream of ERK) as well as via p38 MAPK [168][169][170][171][172]. Other kinases thought to be involved in the IE phase of HCMV infection include adenosine monophosphate-activated protein kinase (AMPK) [173], hematopoietic cell kinase (a src family kinase) [174], cyclin-dependent kinases (CDKs) [175], protein kinase A [176] and mitogen and stress activated kinase (MSK) [128]. The activation of kinase signalling pathways in the initial infection phase comes with multiple, mostly beneficial consequences for the virus including major IE gene activation.…”
Section: Transcriptional Control Of the Major Ie Genementioning
confidence: 99%
See 1 more Smart Citation
“…These pathways include mitogen-activated kinase (MAPK) signalling both via extracellular signal-regulated kinase (ERK) 1 and 2 including RAF1 (MAPKKK upstream of ERK) as well as via p38 MAPK [168][169][170][171][172]. Other kinases thought to be involved in the IE phase of HCMV infection include adenosine monophosphate-activated protein kinase (AMPK) [173], hematopoietic cell kinase (a src family kinase) [174], cyclin-dependent kinases (CDKs) [175], protein kinase A [176] and mitogen and stress activated kinase (MSK) [128]. The activation of kinase signalling pathways in the initial infection phase comes with multiple, mostly beneficial consequences for the virus including major IE gene activation.…”
Section: Transcriptional Control Of the Major Ie Genementioning
confidence: 99%
“…Alternate mechanisms of action are based on the ability of these compounds to modulate cell signalling pathways [370]. For example, cardiac glycoside digitoxin has been reported to inhibit HCMV through induction of cellular autophagy following activation of the regulatory kinase AMPK via a novel NA + ,K + -ATPase subunit α1-AMPK-ULK1 pathway [173]. In addition to inhibiting HCMV, cardiac glycosides act as antivirals against a range of clinically important DNA and RNA viruses.…”
Section: Cardiac Glycosidesmentioning
confidence: 99%
“…HCMV-mediated AMPK activation is dependent on CaMKK, and inhibition of AMPK activity abrogated HCMV replication and DNA synthesis [ 55 ]. Furthermore, the cardiac glycoside digitoxin induces phosphorylation of AMPK/ULK1, whereas it suppresses mTOR activity to increase autophagic flux and inhibit HCMV replication [ 56 ]. Moreover, HCMV induces production of the host protein viperin [ 57 ], which is required for AMPK activation, transcriptional activation of GLUT4 and lipogenic enzymes, and lipid synthesis [ 58 ].…”
Section: Multifaceted Role Of Ampk In Antimicrobial Responsesmentioning
confidence: 99%
“…The mechanism by which cardenolides affect several steps of HSV replication could be related to the inhibition of Na + / K + -ATPase in host cells. Many studies have demonstrated the modulation of Na + /K + -ATPase functions in host cells by DNA viruses (adenoviruses [18], cytomegalovirus [23,[70][71][72], and HSV [27,28]), and RNA viruses (chikungunya virus [19,73], coronaviruses [20,74,75], respiratory syncytial virus [76,77], Ebola virus [78,79], influenza virus [33,80,81], and HIV [30,31,82]). By activating signaling cascades or by altering the concentration of intracellular ions, the binding of cardenolides to Na + /K + -ATPase seems to create an unfavorable environment for viral replication.…”
Section: Discussionmentioning
confidence: 99%